STRATEGI PEMASARAN PADA UMKM FAMILY COOKIES TRENGGALEK DALAM MENINGKATKAN PENJUALAN - Riswanda, Bekti Nita Ayu; Ernestivita, Gesty (Universitas Nusantara PGRI Kediri, 2022)
The right marketing strategy is one of the demands that must be met by business actors, strategy is needed against the background of the current phenomenon with many similar processed products that cause fierce business competition. The goal of a business to be achieved properly is that a company must use the right marketing strategy. Therefore, the strategy to improve marketing for MSMEs Family Cookies Trenggalek is the main goal in this study. A descriptive approach with a qualitative type of research is a research method this time. By using some of the data that has been collected, namely in the form of interviews, observations and documentation. The following is the result of research that has been carried out, namely 1) In carrying out the marketing strategy of MSMEs Family Cookies using the 4P marketing mix of products, prices, promotions and places. 2) MSMEs Family Cookies have carried out a good marketing strategy, because in terms of innovation, it is to provide innovations in the production of cookies. In terms of price, it is to continue to sort for the quality of raw materials but still use low prices. In terms of promotion, it is to use social media and distribution.